Psychometric Analysis of a Postulated Set of Evolved Human Motives - Aunger, Robert; Foster, Dugald; Curtis, Val (Frontiers in Psychology, 2021)
Many different general systems of human motives have been postulated in the psychological literature. However, there is as yet no consensus on which motives should be nominated, nor how many there are. Recently, we deduced the existence of a number of motives using a logical argument derived from evolutionary theory. Here, we confirm the existence of 14 out of 15 of these postulated motives using factor analysis of a web-based sample of 500 respondents from the UK: Lust, Hunger, Fear, Disgust, Attract, Love, Nurture, Hoard, Create, Affiliate, Status, Justice, Curiosity, and Play. The items which loaded strongly for each factor confirmed the expected core value of each motive. Comfort did not emerge, perhaps because it is more physiological in nature. We believe this analysis can form the foundation of a scale for use in applied psychological work ranging from personality testing to personnel selection to public health program design.